Three-phase fast decoupled power flow - Denis, I. F.E.D. [UNESP]; Padilha, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
This paper presents power flow methods for the solution of unbalanced and balanced three-phase distribution systems. The best existing methods for solving three-phase power flow are tested and the results discussed. The fast decoupled methods and the current injection Newton work for radial and meshed networks, and the matrices (Jacobian) are remained constants, but the backwaraforward sweep is appropriated for radial systems and works for weakly meshed network. For general systems, the BX methods have presented the best performance.
Keywords: Decoupled power flow; Distribution system analysis; Unbalanced power flow